High performance release paper and release film, pha-based barrier release coating composition, and preparation method and application thereof
Patent Information
- Application Number
- CN202611415986.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-23
AI Technical Summary
现有技术亦未给出通过离型面表层区与表层区以外区域的绝对质量分配、纸内聚羟基脂肪酸酯微域与纤维素纤维实体的接触关系、离型面桥联区尺寸及投影覆盖率等进一步结构参数协同调节有机硅厚度方向迁移的技术启示,也未涉及上述双区结构在低有机硅干涂布量下对残余粘着率和老化离型稳定性的协同改善
[0061]本发明通过纸内聚羟基脂肪酸酯微域与离型面聚羟基脂肪酸酯桥联区的配合,对有机硅向纸内迁移的通道进行分级调节,使有机硅更多地保留于有效离型界面,在较低目标聚羟基脂肪酸酯和有机硅用量下兼顾残余粘着率与老化离型稳定性。通过控制纸内微域尺寸及片状域比例,减少大尺寸片状聚集造成的空间分布不均;通过在离型面关键孔隙位置形成局部桥联,兼顾材料减量、干燥负荷降低与连续涂布及硅化生产。
Smart Images

Figure CN122960055A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of papermaking, paper surface treatment and release materials, and relates to high-performance release paper and release film, PHA-based barrier coating composition and its preparation method and application. Background Technology
[0002] Release paper typically consists of a cellulose base paper, a sealing or primer structure to improve the release agent retention capacity, and a release layer applied to the adhesive contact surface. Silicone release layers, characterized by low surface energy, adjustable release force, and good thermal stability, are widely used in pressure-sensitive labels, industrial tapes, and die-cutting materials.
[0003] Cellulose base paper is composed of interwoven fibers, with pores, throats, and connecting capillary channels of varying sizes on its surface and interior. When low-viscosity silicone coating liquid is applied to the paper surface, it easily migrates into the paper along these pores, resulting in a decrease in the actual amount of silicone at the adhesive contact surface. To achieve the desired release effect, current production methods typically require increasing the silicone coating amount or pre-setting a higher amount of polymer or inorganic primer. These methods increase material consumption and drying energy consumption, and may cause uneven curing, adhesive surface contamination, and aging release force drift.
[0004] Polyhydroxy fatty acid esters (PHA) are a type of aliphatic polyester with hydrophobicity and certain film-forming ability, and can be used in paper processing in the form of aqueous dispersions.
[0005] PHA possesses hydrophobicity and a certain film-forming ability, and is used in paper processing in the form of an aqueous dispersion. When using two or more target polyhydroxyalkanoates, unless otherwise specified, the amount of the target polyhydroxyalkanoate is the sum of the dry solids masses of each target polyhydroxyalkanoate.
[0006] However, PHA materials are typically more expensive than starch, polyvinyl alcohol (PVA), or inorganic primers. If the traditional continuous film approach is used directly, a high amount of PHA needs to be applied to completely cover the paper surface to effectively prevent silicone from penetrating the paper. This method does not fully utilize the layered structure of paper pores, and PHA tends to form redundant coverage in non-critical areas, resulting in low material utilization.
[0007] US5451456A discloses adding PHB or PHBV latex to a paper fiber suspension, causing PHA particles to adsorb onto the fibers, or applying PHA to the paper surface by coating, impregnation, or spraying, followed by calendering or hot pressing after drying. WO1996024682A1 discloses continuous, partial, or patterned coating of waterborne PHA latex on paper and other substrates, with a PHA layer thickness of approximately 0.5–30 μm, and may contain thickeners, stabilizers, fillers, or other polymers. The above documents disclose the pathways by which PHA enters the fiber network or paper surface through wet-end addition or surface treatment, but do not disclose the application of PHA in the same release paper at a total concentration of 0.25–0.70 g / m³. 2 The target polyhydroxyalkanoate is simultaneously configured as discrete microdomains within the paper and multiple separated or partially connected bridging regions located at fiber intersections, orifices, or throats on the release surface, and a dry coating amount of 0.45–0.75 g / m is provided on the release surface. 2 The addition-clinked silicone release layer. The aforementioned literature also failed to provide technical insights into further regulating the thickness direction migration of silicone through the absolute mass distribution of the two thickness regions, the micro-domain morphology within the paper, and the bridging structure of the release surface.
[0008] US5807781A discloses a release paper and a release liner with a silicate base coating, which uses water glass and water-soluble film-forming materials to reduce the penetration of organosilicon into the paper, and discloses a concentration of approximately 0.5–0.9 g / m³. 2 The amount of silicone coating. WO2020110689A1 discloses release paper with a bio-based resin and / or biodegradable resin stop layer and an outer release agent layer, wherein the stop layer is mainly formed into a continuous resin layer by melt extrusion or lamination. The above solutions all close the paper surface with a continuous or high-coverage bottom layer, and do not disclose the structure in which the migration channel is jointly regulated by low-amount polyhydroxyalkanoate microdomains in the paper and discontinuous polyhydroxyalkanoate bridging regions on the release surface.
[0009] WO2021256381A1 discloses a PHBH and adhesive coating on the surface of a paper substrate, wherein the dry solids mass ratio of PHBH to adhesive is 99.9:0.1 to 60:40, and the dry coating weight is 1 to 50 g / m². 2 It can be set from 3 to 15 g / m 2 The sealing layer. This scheme forms a barrier coating through PHBH, binder, and high coating amount, with the total amount of target polyhydroxyalkanoate not disclosed as 0.25–0.70 g / m³. 2 The paper has a dual-zone distribution structure with the inner and release surfaces.
[0010] CN119777197A discloses a PHA waterborne coating composed of a PHA aqueous dispersion, emulsifier, thickener, film-forming aid, and leveling agent, and discloses its application to paper surface. WO2022003195A1 discloses an aqueous biopolymer dispersion containing PHA, PVA or other stabilizers, rheology modifiers, crosslinking agents, and additives. The above documents mainly concern the dispersion stability, rheology, and continuous film-forming properties of aqueous compositions, but do not disclose a polyhydroxyalkanoate-based barrier coating composition with a solid content of not less than 8 wt% and less than 20 wt%, a target polyhydroxyalkanoate accounting for 91.5 to 99.5 wt% of the dry solids component, and a non-polyhydroxyalkanoate film-forming polymer not exceeding 5 wt% of the dry solids component. Nor do they disclose the application of the above composition in low amounts to the release surface of a cellulose paper base that already contains polyhydroxyalkanoate microdomains within the paper to form multiple separated or partially connected release surface polyhydroxyalkanoate bridging regions located at fiber intersections, orifices, or throats.
[0011] This invention, by controlling the solid content of the polyhydroxyalkanoate-based barrier coating composition, the proportion of the target polyhydroxyalkanoate in the dry solids component, and the content of the non-polyhydroxyalkanoate film-forming polymer, makes the composition suitable for bridging key pore locations on the release surface at a lower application amount. The composition, in conjunction with the polyhydroxyalkanoate microdomains formed within the paper in the wet end, forms microdomains within the paper and a bridging region on the release surface that can be detected in the finished product.
[0012] WO2024194712A1 discloses the manufacture of a fiber substrate using a pulp containing PHA-coated waste paper, and the further application of a PHA-containing dispersion coating, including PHBV, to the surface of the resulting fiber substrate. In this scheme, the in-paper PHA primarily originates from the coated waste paper, while the surface PHA is used to form a paper-based packaging barrier coating. It does not disclose the addition of independently metered target aqueous dispersions of polyhydroxyalkanoates to the wet end, ensuring that the projected area of the in-paper flake-like polyhydroxyalkanoate domains is no more than 5%, nor does it disclose that the surface target polyhydroxyalkanoate content is 0.20–0.55 g / m³. 2 And form release material for the release face throat bridge region.
[0013] The applicant has previously disclosed in CN120250392B a nanoscale paper-based barrier emulsion and a dense barrier coating formed from PHA and PVA. This scheme uses a continuous dense barrier layer as the main structure. In contrast, this invention controls the non-PHA film-forming polymer to within 5 wt% of the total dry solids of the polyhydroxyalkanoate-based barrier coating composition, and regulates the organosilicon migration channels using polyhydroxyalkanoate microdomains within the paper and polyhydroxyalkanoate bridging regions on the release surface.
[0014] The applicant's existing CN120759147B, "Bio-based PHA oil-blocking and moisture-permeable coating for hamburger paper, coated paper and preparation method," discloses an aqueous coating containing semi-crystalline matrix PHA and low-crystallinity or amorphous toughening PHA. After drying and forming a film, a functional gradient structure is formed along the thickness direction of the paper coating, with toughening PHA enriched near the paper-based interface and matrix PHA enriched on the coating surface. This functional gradient is located inside the paper coating and is used to balance the oil-blocking, moisture-permeable, and flexible properties of hamburger packaging paper. However, it does not involve the paper-in-paper polyhydroxyalkanoate microdomains, low-amount release surface polyhydroxyalkanoate bridging regions, and cross-linked silicone release layers formed by wet-end addition.
[0015] In this invention, the wet end and release surface employ the same or different target polyhydroxyalkanoate aqueous dispersions. The wet end target polyhydroxyalkanoate forms discrete microdomains within the cellulose paper matrix, limiting the proportion of large-size sheet-like polyhydroxyalkanoate domains; in a further embodiment, these discrete microdomains primarily contact the cellulose fiber matrix. The release surface target polyhydroxyalkanoate forms multiple bridging regions that are separated or partially connected at fiber intersections, openings, or throats, and a cross-linked silicone release layer is provided on the release surface.
[0016] Existing technologies disclose methods for adding PHA in the wet end, coating PHA on the surface, applying PHA continuously or partially, using biodegradable resin as a stop layer, adding an organosilicon release layer, and creating a multi-component aqueous dispersion of PHA. However, they do not disclose methods for incorporating PHA in the same release paper with a total content of 0.25–0.70 g / m³. 2 The target polyhydroxyalkanoate is simultaneously configured as discrete microdomains within the paper and multiple separated or partially connected bridging regions located at fiber intersections, orifices, or throats on the release surface. The equivalent diameter of the paper-based polyhydroxyalkanoate microdomains (excluding the sheet-like polyhydroxyalkanoate domains) within a region greater than 20%T and not greater than 100%T from the release surface is 0.2–5 μm, and the projected area of the sheet-like polyhydroxyalkanoate domains accounts for no more than 5%. Simultaneously, a dry coating amount of 0.45–0.75 g / m² is applied to the release surface. 2 The existing technology does not provide any technical insights into the synergistic adjustment of silicone thickness direction migration by further structural parameters such as the absolute mass distribution between the release surface region and the region outside the release surface region, the contact relationship between the polyhydroxyalkanoate microdomains in the paper and the cellulose fiber entity, and the size and projection coverage of the release surface bridging region. Nor does it address the synergistic improvement of residual adhesion and aging release stability of the above-mentioned dual-zone structure under low silicone dry coating amount.
[0017] Therefore, it is necessary to provide a high-performance release material with low content of target polyhydroxy fatty acid ester and organosilicon, thickness direction structure that can be detected from the finished product, and which takes into account organosilicon retention, residual adhesion rate and aging release stability. Summary of the Invention
[0018] This invention provides a high-performance release paper and release film, a PHA-based barrier coating composition, its preparation method and application, aiming to reduce the penetration of organosilicon into the paper base, and to balance release stability and adhesive performance of adhesive materials with lower amounts of polyhydroxyalkanoates and organosilicon.
[0019] This invention provides a high-performance release paper, comprising a cellulose paper base and an addition-type cross-linked silicone release layer. The cellulose paper base has a release surface, and the addition-type cross-linked silicone release layer is disposed on the release surface. The cellulose paper base contains one or more polyhydroxyalkanoates, collectively referred to as target polyhydroxyalkanoates. The target polyhydroxyalkanoates form discrete intrapaper polyhydroxyalkanoate microdomains within the cellulose paper base and form multiple release surface polyhydroxyalkanoate bridging regions that are separated from or partially connected to each other on the release surface. The release surface polyhydroxyalkanoate bridging regions are located at fiber intersections, openings, or throats.
[0020] Taking the release surface as the starting point in the thickness direction and the thickness of the cellulose paper base as T, within a region greater than 20%T and not greater than 100%T from the release surface, the spatial unit formed by the target polyhydroxyalkanoate is defined as a target polyhydroxyalkanoate domain. The target polyhydroxyalkanoate domain with a maximum Feretta diameter of not less than 20 μm and an aspect ratio of not less than 5 is defined as a sheet-like polyhydroxyalkanoate domain. Apart from the sheet-like polyhydroxyalkanoate domains, the target polyhydroxyalkanoate exists as in-paper polyhydroxyalkanoate microdomains with an equivalent diameter of 0.2–5 μm. The sum of the projected areas of the sheet-like polyhydroxyalkanoate domains accounts for no more than 5% of the sum of the projected areas of all the target polyhydroxyalkanoate domains within the region.
[0021] The total amount of the target polyhydroxyalkanoate in the cellulose paper base is 0.25–0.70 g / m³. 2 The dry coating weight of the addition-cured crosslinked silicone release layer is 0.45–0.75 g / m². 2 .
[0022] Further, the region no more than 20%T from the release surface is defined as the release surface layer region, and the region more than 20%T but no more than 100%T from the release surface is defined as the region outside the surface layer region. The amount of target polyhydroxyalkanoate in the release surface layer region and the region outside the surface layer region is 0.20~0.55g / m², respectively. 2 and 0.04~0.18g / m 2 The sum of the two satisfies the aforementioned target total amount range of polyhydroxyalkanoates. The quality of the partition is determined quantitatively based on the thickness direction of the finished product.
[0023] In a further embodiment, the mass ratio of the target polyhydroxyalkanoate in the release surface region to that in the regions outside the release surface region is 2 to 8.
[0024] In one specific embodiment, the total amount of the target polyhydroxyalkanoate is 0.30–0.60 g / m³. 2 The amounts of target polyhydroxyalkanoates in the release surface region and in the regions outside the release surface region are 0.24–0.48 g / m² and 0.06–0.14 g / m², respectively. 2 The mass ratio of the two is 2.5 to 6, and the dry coating weight of the addition-cured crosslinked silicone release layer is 0.50 to 0.70 g / m². 2 .
[0025] Furthermore, the region 40%T to 60%T from the release surface is defined as the central region, and the region 80%T to 100%T from the release surface is defined as the back layer region. The unit volume content ratio of the target polyhydroxyalkanoate in the central region to that in the back layer region is 0.80 to 1.25.
[0026] The target total amount of polyhydroxyalkanoate is, for example, 0.25 g / m³. 2 0.28g / m 2 0.30g / m 2 0.32g / m 2 0.35g / m 2 0.38g / m 2 0.40g / m 2 0.42g / m 2 0.45g / m 2 0.48g / m 2 0.50g / m 2 0.52g / m 2 0.55g / m 2 0.58g / m 2 0.60g / m 2 0.62g / m 2 0.65g / m 2 0.68g / m 2 or 0.70g / m 2 .
[0027] The amount of the target polyhydroxyalkanoate in the release surface layer is, for example, 0.20 g / m². 2 0.21g / m 2 0.24g / m 2 0.25g / m 2 0.28g / m 2 0.30g / m2 0.32g / m 2 0.35g / m 2 0.36g / m 2 0.38g / m 2 0.40g / m 2 0.42g / m 2 0.45g / m 2 0.48g / m 2 0.50g / m 2 0.52g / m 2 Or 0.55g / m 2 .
[0028] The amount of the target polyhydroxyalkanoate in the region outside the surface layer is, for example, 0.04 g / m². 2 0.05g / m 2 0.06g / m 2 0.07g / m 2 0.08g / m 2 0.09g / m 2 0.10g / m 2 0.11g / m 2 0.12g / m 2 0.13g / m 2 0.14g / m 2 0.15g / m 2 0.16g / m 2 0.17g / m 2 Or 0.18g / m 2 .
[0029] The ratio of the amount of target polyhydroxyalkanoate in the release surface region to the amount of target polyhydroxyalkanoate in the region outside the release surface region is, for example, 2, 2.2, 2.5, 2.8, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8.
[0030] Furthermore, based on the number of polyhydroxyalkanoate microdomains within the paper, the proportion of the polyhydroxyalkanoate microdomains within the paper that are in contact with the cellulose fiber entity is not less than 70%.
[0031] Furthermore, the equivalent diameter of the polyhydroxyalkanoate bridging region on the release surface is 3–30 μm, and the projection coverage of the target polyhydroxyalkanoate on the release surface is 30%–80%. The projection coverage is calculated based on the projection of the target polyhydroxyalkanoate in the surface region of the release surface along the thickness direction of the paper base onto the release surface.
[0032] In a further embodiment, the exposed fiber area on the release surface accounts for 15% to 60%.
[0033] The target polyhydroxy fatty acid ester is selected from one or more of short-chain polyhydroxy fatty acid esters, medium- and long-chain polyhydroxy fatty acid esters, or copolyesters containing two or more hydroxy fatty acid structural units.
[0034] The short-chain polyhydroxy fatty acid ester is selected from one or more of poly(3-hydroxybutyrate), poly(4-hydroxybutyrate), poly(3-hydroxyvalerate), poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester, and poly(3-hydroxybutyrate-4-hydroxybutyrate) copolyester.
[0035] The medium- and long-chain polyhydroxy fatty acid esters are selected from one or more of poly(3-hydroxyhexanoate), poly(3-hydroxyheptanoate), poly(3-hydroxyoctanoate), poly(3-hydroxynonanoate), poly(3-hydroxydecanoate), poly(3-hydroxyundecanoate), poly(3-hydroxydodecanate), poly(3-hydroxytridecanate), and poly(3-hydroxytetradecanoate).
[0036] The copolyester containing two or more hydroxy fatty acid structural units also includes poly(3-hydroxybutyric acid-3-hydroxyhexanoic acid) copolyester.
[0037] The above material selection applies to the high-performance release paper and the following siliconized release paper and polyhydroxyalkanoate-based barrier coating composition. When using two or more target polyhydroxyalkanoates, the total amount of target polyhydroxyalkanoates is calculated as the sum of the dry solids masses of each target polyhydroxyalkanoate. The wet end and release surface use the same or different target polyhydroxyalkanoates.
[0038] In a further embodiment, the target polyhydroxyalkanoate comprises at least a poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester, wherein the content of 3-hydroxyvalerate structural units is 3–20 mol%. For the high-performance release paper and the release paper to be siliconized, the poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester accounts for no less than 90 wt% of the total mass of all polyhydroxyalkanoates contained in the corresponding materials; for the following polyhydroxyalkanoate-based barrier coating composition, the poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester accounts for no less than 90 wt% of the total mass of the target polyhydroxyalkanoate.
[0039] In one specific implementation, the non-polyhydroxy fatty acid ester film-forming polymer in the release surface layer does not exceed 5 wt% of the total polymer solids in the release surface layer, and the low molecular weight polyol does not exceed 1 wt% of the total polymer solids in the release surface layer.
[0040] This invention also provides a polyhydroxyalkanoate-based barrier coating composition for preparing high-performance release paper with polyhydroxyalkanoate microdomains within the paper and polyhydroxyalkanoate bridging regions on the release surface. The composition is an aqueous composition comprising water and dry solids components, with a solids content of not less than 8 wt% and less than 20 wt%. The dry solids components include the aforementioned target polyhydroxyalkanoate and one or more aqueous coating aids. Based on the total mass of the dry solids components, the content of the target polyhydroxyalkanoate is 91.5–99.5 wt%, and the content of the non-polyhydroxyalkanoate film-forming polymer is not more than 5 wt%.
[0041] Furthermore, the aqueous coating aid is selected from one or more of wetting agents, defoamers, rheology modifiers, non-polyhydroxy fatty acid ester film-forming polymers, and low molecular weight polyols.
[0042] In one specific embodiment, the dry solids component comprises one or more of the following: a target polyhydroxyalkanoate and a wetting agent, a defoamer, a rheology modifier, and a non-polyhydroxyalkanoate film-forming polymer. Based on the total mass of the dry solids component, the target polyhydroxyalkanoate comprises 92.5–99.5 wt%, the wetting agent 0–0.5 wt%, the defoamer 0–0.5 wt%, the rheology modifier 0–1.5 wt%, and the non-polyhydroxyalkanoate film-forming polymer 0–5 wt%, with the sum of the mass percentages of all dry solids components being 100 wt%.
[0043] The solid content of the polyhydroxyalkanoate-based barrier coating composition is, for example, 8 wt%, 9 wt%, 10 wt%, 12 wt%, 15 wt%, 18 wt%, 19 wt%, 19.5 wt%, or 19.9 wt%. The target polyhydroxyalkanoate content, based on the total mass of the dry solids components, is, for example, 91.5 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt%, 97 wt%, 97.5 wt%, 98 wt%, 98.5 wt%, 99 wt%, or 99.5 wt%.
[0044] The mass percentage of not less than 90 wt% is, for example, 90 wt%, 92 wt%, 94 wt%, 95 wt%, 96 wt%, 97 wt%, 98 wt%, 99 wt%, or 100 wt%; the content of the 3-hydroxyvalerate structural unit is, for example, 3 mol%, 5 mol%, 8 mol%, 10 mol%, 12 mol%, 15 mol%, 18 mol%, or 20 mol%.
[0045] The polyhydroxyalkanoate-based barrier coating composition is prepared by mixing a target polyhydroxyalkanoate aqueous dispersion, water, and a selected aqueous coating aid, followed by stirring, solid content adjustment, and filtration.
[0046] The dry coating weight of the addition-cured crosslinked silicone release layer is 0.45–0.75 g / m². 2 The test results of Examples 1-10 show that, under the condition that the polyhydroxyalkanoate microdomains in the paper and the polyhydroxyalkanoate bridging region on the release surface coexist, the extractable silicone mass fraction of the addition-type crosslinked silicone release layer is no more than 5 wt%, the residual adhesion rate of the high-performance release paper is no less than 90%, and the absolute value of the change rate of the release force relative to the initial release force after accelerated aging is no more than 20%.
[0047] The present invention also provides a release paper to be siliconized, comprising a cellulose paper base having a release surface, wherein the release surface constitutes the exposed surface of the release paper to be siliconized. Discrete intracellular polyhydroxyalkanoate microdomains are formed within the cellulose paper base, and multiple release surface polyhydroxyalkanoate bridging regions that are separated from or partially connected to each other are formed at fiber intersections, openings, or throats of the release surface.
[0048] The total amount of the target polyhydroxyalkanoate in the cellulose paper base is 0.25–0.70 g / m³. 2 The statistical regions, size requirements, criteria for determining the sheet-like domains, and the proportion of their projected areas for the polyhydroxyalkanoate microdomains and sheet-like polyhydroxyalkanoate domains within the paper are the same as those for the cellulose paper base of the aforementioned high-performance release paper.
[0049] In a further embodiment, the thickness partitioning and target polyhydroxyalkanoate distribution relationship of the release paper to be siliconized, the contact relationship between the micro-domains in the paper and the cellulose fiber entities, the bridging area size, the projection coverage, the fiber exposed area ratio, and the selection of the target polyhydroxyalkanoate material are respectively implemented using the corresponding embodiments of the aforementioned cellulose paper base.
[0050] The present invention also provides a method for preparing high-performance release paper, including a wet end stage, a release surface treatment stage, and an organosilicon stage.
[0051] In the wet end stage, an aqueous dispersion containing the target polyhydroxy fatty acid ester is added to the fiber slurry. After forming, pressing and drying, the target polyhydroxy fatty acid ester forms discrete polyhydroxy fatty acid ester microdomains within the cellulose paper base, thus obtaining the cellulose paper base.
[0052] In the release surface treatment stage, an aqueous composition containing the target polyhydroxy fatty acid ester is applied to the release surface of the cellulose paper base. After drying and calendering, the target polyhydroxy fatty acid ester forms multiple release surface polyhydroxy fatty acid ester bridging regions that are separated from or partially connected to each other at fiber intersections, openings, or throats, thereby obtaining the release paper to be siliconized.
[0053] In the silicone stage, addition-type crosslinked silicone is applied to and cured on the release surface of the release paper to be siliconeized, forming an addition-type crosslinked silicone release layer, thereby obtaining the high-performance release paper.
[0054] The total dry solids of the target polyhydroxyalkanoate retained in the cellulose paper base during the wet end stage and the release surface treatment stage are 0.25–0.70 g / m³. 2 The dry coating weight of the addition-cured crosslinked silicone release layer is 0.45–0.75 g / m². 2 .
[0055] In one specific embodiment of the wet end stage, an aqueous dispersion of the target polyhydroxyalkanoate is added to the fiber slurry, wherein the dry solids content of the target polyhydroxyalkanoate is 0.08% to 0.35% of the oven-dry fiber mass; subsequently, a fixative and cationic polyacrylamide are added sequentially, followed by a final high-shear treatment, then bentonite is added, and the process is further carried out by forming, pressing, and drying. The initial retention rate of the target polyhydroxyalkanoate is not less than 80%.
[0056] In one specific embodiment of the release surface treatment stage, the polyhydroxyalkanoate-based barrier coating composition is applied to the release surface of a cellulose paper base containing the polyhydroxyalkanoate microdomains within the paper using one of the following methods: anilox roller coating, microgravure coating, coincidence coating, film transfer sizing, or precision spraying. The target polyhydroxyalkanoate dry solids applied and retained on the surface are 0.20–0.55 g / m². 2 After drying and calendering at 80–130°C, the polyhydroxyalkanoate bridging region on the release surface is formed, resulting in the release paper to be siliconized.
[0057] In one specific embodiment of the organosilicon stage, a solvent-free release silicone base polymer, a hydrogen-containing organosilicon crosslinking agent, and a platinum catalyst are mixed and applied to the release surface of the release paper to be siliconized. The addition-type crosslinked organosilicon is then cured by heating to form a dry coating weight of 0.45–0.75 g / m². 2 The addition-type crosslinked silicone release layer.
[0058] The present invention also provides a high-performance release film, comprising the aforementioned high-performance release paper, polymer support film, and composite adhesive layer. The composite adhesive layer is disposed between the polymer support film and the side of the high-performance release paper facing away from the addition-cruising cross-linked silicone release layer, wherein the addition-cruising cross-linked silicone release layer constitutes the release surface of the high-performance release film.
[0059] In one specific embodiment, the polymer support film is a biaxially oriented polyethylene terephthalate film, and the composite adhesive layer is formed by an aliphatic waterborne polyurethane adhesive.
[0060] Compared with the prior art, the use of this invention can achieve the following significant beneficial effects:
[0061] This invention utilizes the interaction between polyhydroxyalkanoate (PHA) microdomains within the paper and the PHA bridging regions on the release surface to hierarchically regulate the migration channels of silicone into the paper. This allows more silicone to remain at the effective release interface, balancing residual adhesion and aging release stability with lower target PHA and silicone dosages. By controlling the size of the microdomains and the proportion of sheet-like domains within the paper, spatial unevenness caused by large-sized sheet aggregation is reduced. Furthermore, by forming local bridging at key pore locations on the release surface, material reduction, lower drying load, and continuous coating and siliconization production are all achieved. Attached Figure Description
[0062] Figure 1 This is a schematic diagram illustrating the preparation process, thickness-direction structure, and mechanism of organosilicon migration barrier and release action of high-performance release paper.
[0063] In the figure, 1-target polyhydroxyalkanoate aqueous dispersion; 2-fiber pulp; 3-polyhydroxyalkanoate microdomain within paper; 4-cellulose paper base; 5-fiber crossover point, orifice or throat; 6-polyhydroxyalkanoate bridging region on release surface; 7-crosslinked silicone; 8-crosslinked silicone release layer; 9-industrial tape. Detailed Implementation
[0064] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this invention should be included within the scope of protection of this invention. Unless otherwise stated, the raw materials used in this embodiment are commercially available industrial products or can be prepared by conventional methods. Unless otherwise specified, performance testing methods are performed according to the "Main Test Standards" and corresponding test methods in this specific embodiment.
[0065] Figure 1 The formation process and mechanism of high-performance release paper are shown.
[0066] In step 1, the target polyhydroxy fatty acid ester aqueous dispersion 1 is added to the fiber slurry 2, and after forming, pressing and drying, the target polyhydroxy fatty acid ester forms a dispersed paper-in-paper polyhydroxy fatty acid ester microdomain 3 inside the cellulose paper base 4.
[0067] In step 2, the target polyhydroxyalkanoate aqueous dispersion 1 is applied to the release surface of the cellulose paper base 4, and by drying and calendering, it forms multiple release surface polyhydroxyalkanoate bridging regions 6 that are separated or partially connected to each other at fiber intersections, openings or throats 5.
[0068] In step 3, cross-linked silicone 7 is applied and cured on the release surface to form a cross-linked silicone release layer 8. The polyhydroxyalkanoate bridging region 6 on the release surface locally bridges the surface pores and throats, and the polyhydroxyalkanoate microdomains 3 within the paper hierarchically regulate the migration channels within the paper, thereby reducing the ineffective migration of cross-linked silicone 7 into the cellulose paper base 4, allowing more of the cross-linked silicone release layer 8 to remain at the effective release interface, and enabling the industrial tape 9 to be stably peeled off along this release interface.
[0069] Table 1. Main reagents and raw materials:
[0070]
[0071] Table 2 Main analytical and testing instruments:
[0072]
[0073] Main testing methods and standards:
[0074] Unless otherwise stated, the International Organization for Standardization (ISO) standards and test methods adopted in this manual are as follows.
[0075] Conditioning and testing atmosphere for paper, paperboard and pulp shall be performed in accordance with ISO 187:2022 "Paper, paperboard and pulp — Standard atmosphere for conditioning and testing and procedures for monitoring and conditioning of samples"; basis weight shall be determined in accordance with ISO 536:2019 "Paper and paperboard — Determination of basis weight"; thickness, density and specific volume shall be determined in accordance with ISO 534:2011 "Paper and paperboard — Determination of thickness, density and specific volume"; moisture content shall be determined in accordance with ISO 287:2017 "Paper and paperboard — Determination of moisture content in a batch of paper — Oven drying method".
[0076] Bendtsen roughness was determined according to ISO 8791-2:2013 "Paper and paperboard—Determination of roughness / smoothness (air leakage method)—Part 2: Bendtsen method"; Gurley air permeability was determined according to ISO 5636-5:2013 "Paper and paperboard—Determination of air permeability (medium range)—Part 5: Gurley method"; Cobb water absorption was determined according to ISO 535:2023 "Paper and paperboard—Determination of water absorption—Cobb method"; tensile properties were determined according to ISO 1924-2:2008 "Paper and paperboard—Determination of tensile properties—Part 2: Constant rate tensile test (20 mm / min)".
[0077] The solid content of the aqueous dispersion was determined in accordance with ISO 3251:2019 "Paints, varnishes and plastics — Determination of nonvolatile content".
[0078] pH was determined according to ISO 976:2013 "Rubber and plastics—Polymer dispersions and latex—Determination of pH". A SevenCompact S220 benchtop pH meter and an InLab Expert Pro-ISM composite electrode were used, and measurements were taken at 25±1℃. Each sample was measured in triplicate.
[0079] Particle size was determined according to ISO 22412:2025, "Particle size analysis—Dynamic light scattering (DLS)". The aqueous dispersion was diluted to 0.05 wt% with deionized water and equilibrated at 25 ± 0.1 °C for 120 s. The particle size distribution was statistically analyzed based on the scattered light intensity. The particle sizes corresponding to a cumulative percentage of 50% and 90% were denoted as D, respectively. 50 and D 90 Each sample was measured in triplicate.
[0080] The viscosity of the aqueous dispersion was determined using a DV2T-LV rotational viscometer. The samples were equilibrated at 25±0.5℃ for 30 min, and the viscosity was measured using an LV-2 rotor at a speed of 60 r / min. The viscosity was read after the rotor ran for 60 s. Each sample was measured in triplicate.
[0081] The content of copolymer structural units in poly(3-hydroxybutyrate-3-hydroxyvalerate), poly(3-hydroxybutyrate-4-hydroxybutyrate), and poly(3-hydroxybutyrate-3-hydroxyhexanoate) copolyesters was determined by proton nuclear magnetic resonance spectroscopy. 20 mg of dried polymer sample was dissolved in 0.7 mL of deuterated chloroform, and proton nuclear magnetic resonance spectra were acquired at 400 MHz. The molar content of the copolymer structural units was calculated based on the integrated area of the characteristic peaks of the corresponding structural units.
[0082] The melting peak temperature of the differential scanning calorimetry (DSC) sample was determined using a DSC 2500 differential scanning calorimeter. 5–10 mg of dry sample was heated from 25 °C to 200 °C at a nitrogen flow rate of 50 mL / min, held at this temperature for 3 min, then cooled to -20 °C at a rate of 10 °C / min, and then heated back to 200 °C at a rate of 10 °C / min. The main melting peak temperature in the second heating curve was taken as the DSC melting peak temperature.
[0083] Release force was determined according to Method 4 of ISO 29862:2024 "Self-adhesive tapes — Determination of peel adhesion properties". The initial release force in Table 8 uses this method as the main test method.
[0084] For target polyhydroxy fatty acid esters other than PHBV or combinations containing two or more target polyhydroxy fatty acid esters, the spatial quantification of the finished product adopts the same confocal Raman microscopy quantification principle as described below for PHBV quantification.
[0085] Before testing, a series of calibration samples with known unit volume contents were prepared using the target polyhydroxyalkanoate actually used in the test sample or a target polyhydroxyalkanoate composition prepared in the same mass ratio as the test sample. The Raman characteristic integral interval of the target polyhydroxyalkanoate relative to the blank cellulose paper base that is distinguishable and does not overlap with the cellulose reference signal was selected to establish the calibration relationship between the total content of target polyhydroxyalkanoate per unit volume and the signal ratio.
[0086] When two or more target polyhydroxyalkanoates are contained, the total content is the sum of the masses of each target polyhydroxyalkanoate. When the characteristic signals of each target polyhydroxyalkanoate overlap, an overall calibration relationship is established using the actual composition. The specific integration intervals, calibration points, and conversion relationships used in the following PHBV examples are as follows.
[0087] Absolute quantification of PHBV thickness was performed using confocal Raman microscopy. Six independent sheets of paper were randomly selected from each sample, and five positions were selected along the horizontal direction of each sheet to prepare cross-sections perpendicular to the release surface, resulting in a total of 30 cross-sectional fields of view. Each field of view was treated as a repeat within a sheet of paper. The average value of each sheet was calculated first, and then the sample mean and standard deviation were calculated using the results of the six sheets of paper.
[0088] Raman spectroscopy was performed using a 532 nm laser with a laser power of 5 ± 0.5 mW on the sample surface. A 50x objective lens was used, with 0.5 μm steps in both the lateral and thickness directions. Cosmic ray removal, fifth-order polynomial baseline subtraction, and intensity normalization were performed on each spectrum. The PHBV signal integration range was 1715–1765 cm⁻¹. -1 The integral range of the cellulose reference signal is 1060–1130 cm⁻¹. -1 The signal-to-weight ratio R is the ratio of the PHBV integral area to the cellulose reference integral area.
[0089] Using cellulose paper bases with the same fiber ratio, beating degree, and sheet density as in the examples, PHBV content per unit volume was prepared at 0 and 0.5 mg / cm³, respectively. 3 1.0 mg / cm 3 2.0 mg / cm 3 5.0 mg / cm 3 10.0 mg / cm 3 20.0 mg / cm 3 and 35.0 mg / cm 3 The calibration sample was used. The calibration relationship between the PHBV content per unit volume (C) and the signal ratio (R) measured using the same parameters was C = 34.80R + 0.06, with a coefficient of determination R0. 2 The value was 0.9976, and the method detection limit was 0.12 mg / cm³. 3The limit of quantitation is 0.40 mg / cm³. 3 .
[0090] The paper base thickness T is measured for each cross-sectional field of view. Pixels located no more than 20%T from the release surface are designated as the release surface area, while pixels located more than 20%T but no more than 100%T from the release surface are designated as the area outside the surface area. The average PHBV per unit volume content for each area is calculated. The absolute mass of PHBV in each area is converted using the formula M = C × t ÷ 1000, where M is in g / m³. 2 The unit of C is mg / cm³ 3 t represents the thickness of the region, in μm.
[0091] The acquisition, segmentation, and calculation of spatial structure parameters are performed according to the following methods.
[0092] The micro-domains and sheet-like polyhydroxyalkanoate (PHA) domains within the paper were statistically analyzed in cross-sectional images of the paper substrate perpendicular to the release surface. The PHA projection coverage, fiber exposed area ratio, and PHA bridging region on the release surface were statistically analyzed in images parallel to the release surface. Target PHA regions were identified using confocal Raman microscopy, flat cross-sections were prepared using focused ion beam scanning electron microscopy, and the morphological boundaries of fibers, pores, and target PHA regions were determined using field emission scanning electron microscopy.
[0093] Raman images and scanning electron microscope images are registered using at least three fiber cross points that can be simultaneously identified in both types of images. The positional residual of each marker point after registration is no greater than 1.0 μm.
[0094] Image analysis used the original 16-bit image. The segmentation threshold was set to the average signal of the blank cellulose paper substrate within the characteristic integral range of the target polyhydroxyalkanoate, plus three times the standard deviation, to form a binary mask of the target polyhydroxyalkanoate. Connectivity between binary targets was determined using an 8-neighborhood algorithm. Targets touching the field of view boundary and those with a projected area less than 0.03 μm were removed. 2 Isolated noise targets.
[0095] The equivalent diameter D of a single target polyhydroxyalkanoate domain eq According to D eq =2×√(A÷π) to calculate, where A is the projected area of the target polyhydroxy fatty acid ester domain in the corresponding statistical plane.
[0096] The maximum Ferete diameter is the maximum distance between two parallel tangents surrounding a single target polyhydroxyalkanoate domain, and the minimum Ferete diameter is the minimum distance between the two parallel tangents. The aspect ratio is the ratio of the maximum Ferete diameter to the minimum Ferete diameter. Target polyhydroxyalkanoate domains with a maximum Ferete diameter of not less than 20 μm and an aspect ratio of not less than 5 are defined as sheet-like polyhydroxyalkanoate domains.
[0097] The polyhydroxyalkanoate (PHA) microdomains within the paper are statistically analyzed within a region greater than 20%T and not greater than 100%T from the release surface. When the registered target PHA binary mask and the cellulose entity mask share at least one boundary pixel, the PHA microdomain within the paper is determined to be in contact with the cellulose fiber entity. The contact rate of the PHA microdomain within the paper is the percentage of the number of PHA microdomains within the paper that are in contact with the cellulose fiber entity out of the total number of PHA microdomains within the paper included in the statistics.
[0098] The percentage of the projected area of the lamellar polyhydroxyalkanoate domain is the ratio of the sum of the projected areas of all lamellar polyhydroxyalkanoate domains in the region outside the surface region to the sum of the projected areas of all target polyhydroxyalkanoate domains in that region.
[0099] The release surface polyhydroxyalkanoate (PHA) projection coverage is calculated by projecting the three-dimensional signal of the target PHA in a region no more than 20%T from the release surface onto the release surface plane along the paper thickness direction. Projected pixels having at least one positive PHA voxel along the thickness direction are counted as target PHA coverage pixels. The ratio of the area of the target PHA coverage pixels to the effective field of view area is the release surface PHA projection coverage.
[0100] The fiber exposure area percentage is calculated based on the registration results of the release surface scanning electron microscope (SEM) image and the Raman image. Pixels with exposed cellulose solid signals that are not covered by the target polyhydroxyalkanoate projection mask are counted as fiber exposed pixels; porous regions are not included in the fiber exposed pixel count. The ratio of the fiber exposed pixel area to the effective field of view area is the fiber exposed area percentage.
[0101] A fiber intersection point refers to the area in a release surface projection image where two or more fibers, whose boundaries or center directions can be traced, overlap or intersect each other. An orifice refers to a pore opening that connects the release surface to the external space and is enclosed by the fiber's solid boundary. A pore throat refers to the region where, as the pore channel connecting to the orifice extends into the paper substrate, the equivalent width of the pore forms a local minimum relative to its preceding and following adjacent pore segments.
[0102] When a target polyhydroxyalkanoate domain simultaneously contacts at least two fiber entity boundaries forming a fiber intersection, orifice, or throat, or crosses the opposite two sides of the orifice or throat, it is identified as a release surface polyhydroxyalkanoate bridging region.
[0103] For connected target polyhydroxyalkanoate regions with two or more local maxima, a watershed method using local maxima as markers is employed to divide bridging regions. Bridging regions that are not interconnected in the original binary mask are considered separated; bridging regions that remain connected through local necks in the original binary mask are considered partially connected. The equivalent diameter of each bridging region is calculated separately.
[0104] The size distribution of the polyhydroxyalkanoate microdomains within the paper and the polyhydroxyalkanoate bridging region on the release surface were calculated based on the number of targets included in the statistics. The equivalent diameters of each target were arranged from smallest to largest, and the equivalent diameters corresponding to the cumulative number of targets reaching 10%, 50%, and 90% of the total number of targets were denoted as P. 10 Median and P 90 P in Tables 4 and 5 10 ~P 90 The range is from the 10th percentile to the 90th percentile calculated based on the target quantity.
[0105] When the Raman characteristic signals of different target polyhydroxyalkanoates are different, a binary mask is established using the corresponding target polyhydroxyalkanoate calibrator and characteristic integration interval; when more than two target polyhydroxyalkanoates are used, the union of the masks of each target polyhydroxyalkanoate is taken as the total mask of the target polyhydroxyalkanoate, and the spatial structure parameters are calculated according to the above method.
[0106] The FINAT test method (FTM) 7 referred to in this document refers to the method listed in the 11th edition (2025) of the FINAT Technical Handbook. The silicone coating weight was determined using energy-dispersive X-ray fluorescence spectrometry according to FTM 7. The initial release force was determined according to Method 4 of ISO 29862:2024, and the residual adhesion was determined according to the test procedure specified in Application Example 3 below.
[0107] The conditions for accelerated aging described in this manual, namely, 70°C dry heat for 168 hours and 50°C and 90% relative humidity for 168 hours, are the conditions set by this manual.
[0108] General preparation method of polyhydroxy fatty acid ester-based barrier coating compositions:
[0109] Under stirring conditions of 300–800 r / min, the target polyhydroxy fatty acid ester aqueous dispersion is mixed with 50%–80% of the total amount of added water for 5–15 min; then, wetting agent, defoamer, non-polyhydroxy fatty acid ester film-forming polymer and low molecular weight polyol (not present in the formulation) are added sequentially, and stirring is continued for 3–10 min after each addition of a component; then, rheology modifier (not present in the formulation) and the remaining added water are added, and stirring is continued for 10–30 min. The solid content of the resulting aqueous composition is adjusted to 8–25 wt% according to the specific surface treatment process, and filtered through a 100–200 mesh filter to obtain an aqueous composition containing the target polyhydroxy fatty acid ester.
[0110] When using two or more target polyhydroxyalkanoate aqueous dispersions, the sum of the dry solids masses of each target polyhydroxyalkanoate is taken as the total target polyhydroxyalkanoate. Each auxiliary component is measured in a non-overlapping category; when the same substance or the same commercial adjuvant has two or more functions, it is counted in only one component category according to its main function in the formulation, and the carrier or associated components contained in the commercial adjuvant are not measured repeatedly.
[0111] Specific examples of preparation of polyhydroxyalkanoate-based barrier coating compositions:
[0112] Taking the preparation of 100,000 kg of a polyhydroxyalkanoate-based barrier coating composition with a solid content of 15.0 wt% as an example, the total dry solids in the composition are 15,000 kg. This formulation example is based on a formula of 50.0 wt% effective content of SURFYNOL 104E, 96.0 wt% non-volatile content of BYK-024, and 20.0 wt% solid content of RHEOLATE 212.
[0113] Weigh out 49.415 kg of BioTen 1031, 0.090 kg of SURFYNOL 104E, 0.03125 kg of BYK-024, 0.750 kg of RHEOLATE 212, and 49.71375 kg of deionized water. BioTen 1031 provides 14.775 kg of non-volatile matter, SURFYNOL 104E provides 0.045 kg of wetting agent, BYK-024 provides 0.030 kg of non-volatile defoamer, and RHEOLATE 212 provides 0.150 kg of non-volatile rheology modifier. This formulation does not require the addition of non-polyhydroxyalkanoate film-forming polymers or low-molecular-weight polyols.
[0114] First, mix 32.314 kg of deionized water and 49.415 kg of BioTen 1031 at 500 r / min for 10 min; while maintaining 500 r / min, add 0.090 kg of SURFYNOL 104E and stir for 5 min, then add 0.03125 kg of BYK-024 and stir for 5 min; add 0.750 kg of RHEOLATE 212 and 17.400 kg of the remaining deionized water, and continue stirring for 20 min. Filter the mixture through a 150-mesh filter and adjust the total mass of the composition to 100.000 kg with deionized water to obtain the polyhydroxyalkanoate-based barrier coating composition.
[0115] The solid content of the resulting composition is 15.0 wt%. Based on the total dry solids of the composition, the poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester is 97.87 wt%, the non-polyhydroxyalkanoate film-forming polymer is 0.33 wt%, which is polyvinyl alcohol introduced by BioTen 1031; the wetting agent is 0.50 wt%, the defoamer is 0.30 wt%, and the rheology modifier is 1.00 wt%. No additional non-polyhydroxyalkanoate film-forming polymer or low molecular weight polyol was added in this formulation.
[0116] When a commercial additive is a multi-component product, it is treated as a single feed component and classified into one component category according to its primary function. The carrier or associated components contained in the commercial additive are not repeatedly classified into other categories. This composition is used for release surface treatment in Examples 1-10.
[0117] General preparation process for high-performance release paper:
[0118] The target polyhydroxyalkanoates are added to the fiber slurry and applied to the release surface in the form of aqueous dispersions, either individually or in combination. When two or more target polyhydroxyalkanoates are used, the wet-end addition amount, the surface application and retention amount, and the total amount are all calculated as the sum of the dry solids mass of each target polyhydroxyalkanoate. Based on the crystallization and thermal softening characteristics of the target polyhydroxyalkanoates used, the process is adjusted within the drying and calendering conditions described in this invention to form discrete intracellular polyhydroxyalkanoate microdomains within the cellulose paper base of the finished product, and to form multiple separated or partially connected release surface polyhydroxyalkanoate bridging regions at fiber intersections, orifices, or throats on the release surface.
[0119] In the region that is greater than 20%T and not greater than 100%T from the release surface, except for the sheet-like polyhydroxyalkanoate domains, the equivalent diameter of the polyhydroxyalkanoate microdomains in the paper is 0.2 to 5 μm, and the sum of the projected areas of the sheet-like polyhydroxyalkanoate domains accounts for no more than 5% of the sum of the projected areas of all target polyhydroxyalkanoate domains in the region.
[0120] In embodiments employing further quantification, the resulting finished product also satisfies the following criteria: absolute mass distribution in the thickness direction, contact rate between polyhydroxyalkanoate microdomains and cellulose fiber entities within the paper, size of the polyhydroxyalkanoate bridging region on the release surface, projected coverage, and percentage of exposed fiber area. Whether a corresponding spatial structure is formed is determined based on the results obtained from the finished product using the aforementioned testing methods.
[0121] BioTen 1030: Target polyhydroxy fatty acid ester is poly(3-hydroxybutyrate); copolymer structural unit content is not applicable; solid content is 30.0 wt%; pH is 7.1; D 50 It is 0.50μm; D 90 The viscosity at 25℃ is 170 mPa·s; the melting peak temperature by differential scanning calorimetry is 174.2℃; and the proportion of polymeric stable components in non-volatile matter is 0.33 wt%.
[0122] BioTen 1031: The target polyhydroxyalkanoate is a poly(3-hydroxybutyric acid-3-hydroxyvalerate) copolyester; the content of 3-hydroxyvalerate structural units is 10.4 mol%; the solid content is 29.9 wt%; the pH is 7.2; D 50 It is 0.48μm; D 90 The viscosity at 25℃ is 165 mPa·s; the melting peak temperature by differential scanning calorimetry is 149.8℃; and the proportion of polymeric stable components in non-volatile matter is 0.33 wt%.
[0123] BioTen 1032: The target polyhydroxyalkanoate is a poly(3-hydroxybutyric acid-4-hydroxybutyric acid) copolyester; the content of 4-hydroxybutyric acid structural units is 12.0 mol%; the solid content is 30.1 wt%; the pH is 7.3; D 50 It is 0.46 μm; D 90 The viscosity at 25℃ is 160 mPa·s; the melting peak temperature by differential scanning calorimetry is 152.6℃; and the proportion of polymeric stable components in non-volatile matter is 0.33 wt%.
[0124] BioTen 1033: The target polyhydroxy fatty acid ester is a poly(3-hydroxybutyric acid-3-hydroxyhexanoic acid) copolyester; the content of 3-hydroxyhexanoic acid structural units is 11.2 mol%; the solid content is 29.8 wt%; the pH is 7.1; D 50 It is 0.54μm; D 90 The viscosity at 25℃ is 175 mPa·s; the melting peak temperature by differential scanning calorimetry is 126.8℃; and the proportion of polymeric stable components in non-volatile matter is 0.33 wt%.
[0125] BioTen 1031 is the target polyhydroxy fatty acid ester aqueous dispersion actually used in Examples 1-10; BioTen 1030, BioTen 1032 and BioTen 1033 are optional commercial raw materials for other target polyhydroxy fatty acid esters.
[0126] In BioTen 1030, BioTen 1031, BioTen 1032, and BioTen 1033, the target polyhydroxyalkanoates all accounted for 99.37 wt% of the total non-volatile matter in the dispersions, polyvinyl alcohol-type polymer stabilizing components accounted for 0.33 wt%, acetylsene glycol wetting agents accounted for 0.20 wt%, aqueous defoamers accounted for 0.10 wt%, and the mass fraction of low molecular weight polyols was 0. After standing at 25°C for 30 days, none of the four aqueous dispersions showed any hard precipitate, and all recovered to a uniform dispersion state after stirring at 300 rpm for 5 minutes.
[0127] The following examples use poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester as the representative material of the target polyhydroxyalkanoate, and the aqueous dispersion used is BioTen 1031. By total mass of the dispersion, BioTen 1031 comprises 29.75 wt% poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester, 0.10 wt% polyvinyl alcohol, 0.06 wt% acetylenol wetting agent, 0.03 wt% aqueous defoamer, and 70.06 wt% deionized water; by total non-volatile matter of the dispersion, poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester is 99.37 wt%, polyvinyl alcohol is 0.33 wt%, acetylenol wetting agent is 0.20 wt%, aqueous defoamer is 0.10 wt%, and the mass fraction of low molecular weight polyol is 0.
[0128] Bleached softwood sulfate pulp and bleached eucalyptus sulfate pulp (BEKP) were mixed at an oven-dry weight ratio of 30:70, and the mixture was decomposed at a weight concentration of 2.0 wt% for 20 min. The pulp was then refined to 35 ± 2°SR using a PFI refiner and diluted to 0.70 wt%.
[0129] Step 1: Add the aqueous dispersion of poly(3-hydroxybutyric acid-3-hydroxyvalerate) copolyester to the fiber slurry under stirring at 500 rpm, and continue stirring for 120 s; add 0.06 wt% (by weight of oven-dried fiber) of fixative, and stir for 30 s; add 0.03 wt% (by weight of oven-dried fiber) of cationic polyacrylamide, and stir for 20 s; increase the speed to 1500 rpm and shear for 30 s; decrease the speed to 500 rpm, add 0.10 wt% (by weight of oven-dried fiber) of bentonite, and stir for 20 s. Prepare a 60 ± 2 g / m³ sheet using a sheet forming device. 2The paper sheet was pressed at 0.40 MPa for 5 min and dried at 105±3℃ to a moisture content of 5% to 7%, yielding a cellulose paper base containing PHBV microdomains within the paper.
[0130] Step 2: BioTen 1031 is formulated into a polyhydroxyalkanoate-based barrier coating composition with a solid content of 15.0 ± 0.5 wt%, which is then applied as a surface working liquid for the poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester to the release surface of the cellulose paper base obtained in Step 1. Based on the total dry solids of the working liquid, the working liquid comprises 98.5 parts of non-volatile components of BioTen 1031, 0.3 parts of acetylenic glycol wetting agent, 0.2 parts of aqueous defoamer, and 1.0 part of rheology modifier; after conversion, the dry solids of the working liquid comprise 97.87 wt% poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester, 0.33 wt% polyvinyl alcohol, 0.50 wt% wetting agent, 0.30 wt% defoamer, and 1.00 wt% rheology modifier, with a low molecular weight polyol mass fraction of 0.
[0131] The coating speed is 10m / min. After coating, the paper is dried at 80℃, 100℃ and 120℃ for 30s each, and then calendered once at 85℃ and 50kN / m to form a release surface PHBV bridging zone at fiber intersections, openings or throats, thus obtaining the release paper to be siliconized.
[0132] Step 3: Mix the solvent-free release silicone base polymer, hydrogen-containing organosilicon crosslinking agent and platinum catalyst at a mass ratio of 100:4:1 for 5 min, let stand to degas for 10 min, and apply it to the release surface of the release paper to be siliconized obtained in Step 2 within 30 min. Cure at 150±3℃ for 30 s to obtain high-performance release paper.
[0133] Example:
[0134] The wet-end addition route retention amount, surface application and retention amount and their mass ratio listed in Examples 1 to 10 are process accounting values of the preparation process; the PHBV mass and their mass ratio of the 0-20%T region and the >20%T-100%T region listed in Table 3 are Raman absolute quantitative values measured by thickness partitioning after the finished product is dried and calendered.
[0135] Because the process accounting boundary and the finished product thickness partition boundary and statistical caliber are different, the two sets of values are used to characterize the process application path and the spatial distribution of the finished product, respectively. For example, the process mass ratio of Example 2 is 8.00, and the finished product partition mass ratio is 6.20; the surface application and retention amount of Example 9 is 0.24 g / m². 2 The measured value of the finished product in the 0-20%T region was 0.238 ± 0.003 g / m³. 2 .
[0136] Example 1: Prepared according to the general preparation process of high-performance release paper, the PHBV retained in the wet end addition route is 0.04 g / m 2 The surface-applied and retained PHBV dry solids content was 0.21 g / m³. 2 The combined value of the two is 0.25 g / m 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route is 5.25, and the dry coating weight of the crosslinked silicone release layer is 0.60 g / m². 2 .
[0137] Example 2: Prepared according to the general preparation process of high-performance release paper, the PHBV retained in the wet end addition route is 0.04 g / m 2 The surface-applied and retained PHBV dry solids content was 0.32 g / m³. 2 The combined value of the two is 0.36 g / m³. 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route is 8.00, and the dry coating weight of the crosslinked silicone release layer is 0.55 g / m². 2 .
[0138] Example 3: Prepared according to the general preparation process of high-performance release paper, the PHBV retained in the wet end addition route is 0.10 g / m 2 The surface-applied and retained PHBV dry solids content is 0.20 g / m³. 2 The combined value of the two is 0.30 g / m 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route is 2.00, and the dry coating weight of the crosslinked silicone release layer is 0.55 g / m². 2 .
[0139] Example 4: Prepared according to the general preparation process of high-performance release paper, the PHBV retained in the wet end addition route is 0.18 g / m 2 The surface-applied and retained PHBV dry solids content was 0.36 g / m³. 2 The combined value of the two is 0.54 g / m 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route is 2.00, and the dry coating weight of the crosslinked silicone release layer is 0.55 g / m². 2 .
[0140] Example 5: Prepared according to the general preparation process of high-performance release paper, the PHBV retained in the wet end addition route is 0.15 g / m 2 The surface-applied and retained PHBV dry solids content is 0.55 g / m³. 2 The combined value of the two is 0.70 g / m³. 2The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route was 3.67, and the dry coating weight of the crosslinked silicone release layer was 0.70 g / m². 2 .
[0141] Example 6: Prepared according to the general preparation process of high-performance release paper, the PHBV retained in the wet end addition route is 0.10 g / m 2 The surface-applied and retained PHBV dry solids content was 0.35 g / m³. 2 The combined value of the two is 0.45 g / m 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route is 3.50, and the dry coating weight of the crosslinked silicone release layer is 0.60 g / m². 2 .
[0142] Example 7: Prepared according to the general preparation process of high-performance release paper, the PHBV retained in the wet end addition route is 0.08 g / m 2 The surface-applied and retained PHBV dry solids content is 0.30 g / m³. 2 The combined value of the two is 0.38 g / m³. 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route is 3.75, and the dry coating weight of the crosslinked silicone release layer is 0.45 g / m². 2 .
[0143] Example 8: Prepared according to the general preparation process of high-performance release paper, the PHBV retained in the wet end addition route is 0.14 g / m 2 The surface-applied and retained PHBV dry solids content was 0.48 g / m³. 2 The combined value of the two is 0.62 g / m 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route was 3.43, and the dry coating weight of the crosslinked silicone release layer was 0.75 g / m². 2 .
[0144] Example 9: Prepared according to the general preparation process of high-performance release paper, the calender pressure was adjusted to 35 kN / m and calendered once; the PHBV retained in the wet end addition route was 0.06 g / m. 2 The surface-applied and retained PHBV dry solids content was 0.24 g / m³. 2 The combined value of the two is 0.30 g / m 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route is 4.00, and the dry coating weight of the crosslinked silicone release layer is 0.50 g / m². 2 .
[0145] Example 10: Prepared according to the general preparation process of high-performance release paper, the calender pressure was adjusted to 70 kN / m and calendered once; the PHBV retained in the wet end addition route was 0.12 g / m. 2 The surface-applied and retained PHBV dry solids content was 0.48 g / m³. 2 The combined value of the two is 0.60 g / m³. 2 The mass ratio of the amount applied and retained on the surface to the amount retained along the wet-end application route is 4.00, and the dry coating weight of the crosslinked silicone release layer is 0.65 g / m². 2 .
[0146] Example 11: Preparation of high-performance release film.
[0147] The high-performance release paper prepared in Example 6 was used as the release paper layer. A Lumirror S10 biaxially oriented polyethylene terephthalate film with a nominal thickness of 50 μm was used as the polymer support film, with a measured thickness of 50 ± 2 μm. The composite surface of the polymer support film was subjected to corona treatment before use to achieve a surface tension of 42 mN / m before lamination.
[0148] NeoRez R-9621 aliphatic waterborne polyurethane dispersion was used as the composite adhesive, and the dry coating weight of the adhesive was controlled at 2.5 ± 0.2 g / m² based on non-volatile matter. 2 The composite adhesive was applied to the corona-treated surface of the polymer support film and dried at 80°C, 100°C, and 110°C for 20 seconds each. Then, the coated surface of the polymer support film was bonded to the side of the high-performance release paper from Example 6 that was opposite to the cross-linked silicone release layer. Roll pressing was performed at 60±3°C, 0.30±0.02MPa, and 10m / min, and the film was cured at 40±2°C for 24 hours to obtain the high-performance release film.
[0149] The resulting high-performance release film comprises, in sequence along the thickness direction, a cross-linked silicone release layer, a cellulose paper base containing a release surface PHBV bridging region and PHBV microdomains within the paper, an aqueous polyurethane composite adhesive layer, and a biaxially stretched polyethylene terephthalate support film; the cross-linked silicone release layer constitutes the exposed release surface of the high-performance release film.
[0150] Comparative example:
[0151] Unless otherwise specified in the comparative examples, Comparative Examples 1 to 12 are based on Example 6. The pulp type and ratio, beating degree, pulp concentration, paper basis weight, fixative, type, amount and order of addition of cationic polyacrylamide and bentonite, wet end shearing conditions, as well as forming, pressing and drying conditions are the same as in Example 6.
[0152] The additives and their proportions, coating speed, segmented drying conditions, calendering conditions, crosslinked silicone formulations, mixing and curing conditions of the surface working liquids in each comparative example are the same as in Example 6. Steps explicitly omitted in the comparative examples are not performed; changes to the source of raw materials, application path, dosage, number of coatings, calendering conditions, or silicone dry coating amount are performed according to the corresponding comparative example.
[0153] Comparative Example 1: Based on Example 6, the wet end and surface PHBV were eliminated. Silicone was directly applied and cured onto the release surface of the cellulose paper base, and the dry coating weight of the crosslinked silicone release layer was adjusted to 0.75 g / m². 2 .
[0154] Comparative Example 2: Based on Example 6, the PHBV was entirely contained within the paper, resulting in a PHBV concentration of 0.45 g / m³. 2 And the application of PHBV on the release surface is cancelled; the dry coating weight of the cross-linked silicone release layer is 0.60 g / m². 2 .
[0155] Comparative Example 3: Based on Example 6, the wet PHBV was removed, and all PHBV was applied to the release surface, resulting in a dry solid content of 0.45 g / m² of PHBV applied and retained on the release surface. 2 The dry coating weight of the cross-linked silicone release layer is 0.60 g / m². 2 .
[0156] Comparative Example 4: Based on Example 6, only the application of surface PHBV in stages and the calendering method were changed. The PHBV remaining in the wet-end application path was 0.10 g / m. 2 The surface PHBV was applied in two applications, with each application retaining 0.175 g / m². 2 The surface was then calendered twice at 110℃ and 100kN / m. The total dry solids of PHBV applied and retained on the surface amounted to 0.35g / m. 2 The resulting release surface has a PHBV projection coverage of no less than 90%, and the exposed fiber area accounts for no more than 5%; the dry coating weight of the cross-linked silicone release layer is 0.60 g / m². 2 .
[0157] Comparative Example 5: Based on Example 6, wet-end PHBV was eliminated, and the dry solids of PHBV applied and retained at the release surface were increased to 1.20 g / m². 2 A continuous film with a thickness of approximately 0.95–1.10 μm is formed; the dry coating weight of the cross-linked silicone release layer is 0.60 g / m². 2 .
[0158] Comparative Example 6: Based on Example 6, only the wet-end PHBV source was changed to coated pulp containing a PHBV film. A 6.0 g / m² coating was pre-applied to the surface of the cellulose base paper.2 PHBV was added and calendered to form a continuous coated paper. This continuous coated paper was cut into 20mm × 20mm fragments and loosened at 3000 r / min for 5 min at a concentration of 2.0 wt% to obtain a coated waste pulp containing PHBV films. Based on the measured PHBV content, the coated waste pulp was added to fresh pulp to achieve a PHBV content of 0.10 g / m³ in the paper. 2 Subsequently, 0.35 g / m² was applied to and retained on the release surface. 2 The PHBV dry solid was formed, and a dry coating weight of 0.60 g / m² was achieved. 2 The cross-linked silicone release layer.
[0159] Comparative Example 7: Based on Example 6, only the PHBV in the paper was reduced to 0.02 g / m³. 2 The surface-applied and retained PHBV dry solids content was 0.35 g / m³. 2 The dry coating weight of the cross-linked silicone release layer is 0.60 g / m². 2 .
[0160] Comparative Example 8: Based on Example 6, only the surface-applied and retained PHBV dry solids were reduced to 0.12 g / m³. 2 The PHBV in the paper is 0.10 g / m³. 2 The dry coating weight of the cross-linked silicone release layer is 0.60 g / m². 2 .
[0161] Comparative Example 9: Based on Example 6, the amount of PHBV used in the paper's interior and surface was increased to achieve an interior PHBV of 0.20 g / m³. 2 The surface-applied and retained PHBV dry solids content is 0.70 g / m³. 2 The dry coating weight of the cross-linked silicone release layer is 0.60 g / m². 2 .
[0162] Comparative Example 10: Based on Example 6, only the dry coating amount of the crosslinked silicone release layer was adjusted to 0.35 g / m². 2 The amount of PHBV and the spatial structure are the same as in Example 6.
[0163] Comparative Example 11: Based on Example 6, the wet-end PHBV and PHBV surface working solution were omitted and replaced with a primer solution composed of polyvinyl alcohol and oxidized starch. The polyvinyl alcohol and oxidized starch were prepared at a dry solids mass ratio of 50:50, resulting in a dry coating weight of 0.60 g / m² on the release surface of the cellulose paper base. 2 A base coating is then applied; subsequently, a dry coating with a coverage of 0.60 g / m² is formed. 2 The cross-linked silicone release layer.
[0164] Comparative Example 12: Based on Example 6, the wet-end PHBV and PHBV surface working solution were omitted and replaced with a primer solution composed of water glass and polyvinyl alcohol. The modulus of the water glass was 3.2 ± 0.1, and the water glass and polyvinyl alcohol were prepared at a dry solids mass ratio of 80:20, resulting in a dry coating weight of 0.60 g / m² on the release surface of the cellulose paper base. 2 A base coating is then applied; subsequently, a dry coating with a coverage of 0.60 g / m² is formed. 2 The cross-linked silicone release layer.
[0165] Application Example 1: Spatial Structure Characterization of PHBV.
[0166] Experimental Description: Examples 1-10 were conditioned at 23±1℃ and 50±2% relative humidity for at least 24 hours. The absolute mass of PHBV thickness zones was determined according to the aforementioned confocal Raman microscopy absolute quantitative method. The coverage of PHBV micro-domains within the paper, sheet-like PHBV domains, PHBV bridging areas on the release surface, PHBV projection coverage on the release surface, and fiber exposed area ratio were determined according to the aforementioned spatial structure parameter detection method.
[0167] In the tests of the in-paper PHBV micro-domain and sheet-like PHBV domain, three independent sheets of paper were randomly selected for each example, and ten cross-sectional fields of view were randomly selected for each sheet, for a total of 30 cross-sectional fields of view. The effective analysis area of each field of view was 80μm×80μm.
[0168] In the tests of release surface PHBV bridging area, release surface PHBV projection coverage and fiber exposed area ratio, three independent sheets of paper were randomly selected for each example, and eight release surface fields of view were randomly selected for each sheet, for a total of 24 release surface fields of view. The effective analysis area of each field of view was 150μm×150μm.
[0169] The area 40%T to 60%T from the release surface was designated as the central region, and the area 80%T to 100%T from the release surface was designated as the back layer region. The PHBV content per unit volume was calculated pixel-by-pixel using the aforementioned Raman calibration curve. Three independent sheets were tested in each embodiment, with five cross-sectional fields of view for each sheet. First, the average value and ratio of the central and back layer regions for each sheet were calculated. Then, the sample mean and standard deviation were calculated based on the results of the three independent sheets.
[0170] Table 3. Actual measurement results of absolute mass of PHBV thickness zones:
[0171]
[0172] Note: The paper base thickness T is the average value of 30 cross-sectional fields of view; the PHBV quality column is the average value ± standard deviation calculated by first taking the average value of 5 fields of view per sheet, and then the result of 6 independent sheets; the quality ratio between the two regions is calculated as the ratio of the average quality of the corresponding regions.
[0173] Table 4. Measured results of PHBV micro-domain size in paper:
[0174]
[0175] Table 5. Measured dimensions of the PHBV bridging zone on the release surface:
[0176]
[0177] Table 6. Measured results of PHBV content per unit volume in the central and back layers:
[0178]
[0179] Table 7. Comprehensive characterization results of PHBV spatial structure:
[0180]
[0181] Analysis: Tables 3 to 7 show that the PHBV mass in the 0-20%T region of the finished products from Examples 1 to 10 is 0.202-0.545 g / m³. 2 The PHBV mass in the region >20%T to 100%T is 0.045 to 0.175 g / m³. 2 The total PHBV level is 0.250–0.700 g / m³. 2 The quality ratio between the two regions is 2.06 to 6.20, and the actual measured total of the finished product is consistent with the total calculated by the corresponding process.
[0182] The equivalent diameter of the PHBV microdomains within the paper ranges from 0.20 to 4.96 μm, with 74% to 89% of the microdomains in contact with the cellulose fiber matrix, and the projected area of sheet-like PHBV domains accounting for 1.5% to 4.2%. The equivalent diameter of the PHBV bridging region on the release surface ranges from 3.0 to 29.9 μm. The projected coverage of PHBV on the release surface ranges from 31% to 80%, with the fiber exposed area accounting for 15% to 59%, and the PHBV volume ratio between the central region and the backing layer ranges from 0.92 to 1.12.
[0183] The above results indicate that the PHBV added in the wet end mainly forms discrete microdomains within the paper that come into contact with the fibers, while the PHBV applied to the release surface mainly forms discontinuous bridging regions that retain the exposed fiber areas. Examples 9 and 10 yielded release surface PHBV projection coverage of 31% and 80%, and fiber exposed area ratios of 59% and 15%, respectively, verifying the corresponding boundaries of the surface structure range.
[0184] Application Example 2: Initial Release Performance.
[0185] Experimental Description: Examples 1-10 and Comparative Examples 1-12 were conditioned at 23±1℃ and 50±2% relative humidity for at least 24 hours, and then cut into 25mm wide samples along the same direction. The initial release force in Table 8 was determined according to Method 4 of ISO 29862:2024.
[0186] The test used tesa 7475 PV2 silicone release coating test tape. The tape was conditioned at 23±1℃ and 50±2% relative humidity and cut longitudinally to a width of 25.0±0.2mm. The tape was applied to the silicone surface and rolled twice back and forth at a speed of 10mm / s using a standard rubber roller with a weight of 2.00±0.01kg and a surface hardness of 80±5 Shore A. The tape was then left to stand at 23±1℃ and 50±2% relative humidity for 20 minutes. Subsequently, a universal testing machine was used to test the tape at a peel speed of 300mm / min with a 180° peel angle. Five tapes were tested for each sample.
[0187] Record the average release force, standard deviation, and peel peak value. Calculate the coefficient of variation by dividing the standard deviation by the average release force and multiplying by 100%. Simultaneously observe interface damage modes such as fiber tearing, adhesive transfer, silicone transfer, substrate exposure, and localized high peeling.
[0188] Table 8 Initial release performance test results:
[0189]
[0190] Analysis: The initial release forces of Examples 1-10 ranged from 18.4 to 29.6 cN / 25 mm, with coefficients of variation ranging from 4.2% to 7.8%, and no fiber tearing or adhesive transfer was observed. Compared with Comparative Examples 2 and 3, which had the same total PHBV and silicone dry coating amount, Example 6 showed a decrease in initial release force from 32.8 cN / 25 mm and 25.6 cN / 25 mm to 21.4 cN / 25 mm, respectively, and a decrease in coefficients of variation from 9.7% and 6.6% to 4.3%, respectively, indicating that the dual-zone distribution structure is beneficial for forming a uniform release interface.
[0191] Comparative Example 8 exhibited substrate exposure and adhesive transfer due to insufficient PHBV on the release surface, while Comparative Example 10 showed significant substrate exposure due to insufficient dry silicone coating. Although Comparative Examples 5 and 9 had relatively low initial release forces, their total PHBV was only 1.20 g / m². 2 and 0.90g / m 2 The reduction in material usage was not reflected.
[0192] Application Example 3: Residual Adhesion Rate.
[0193] Experimental Description: Examples 1-10 and Comparative Examples 1-12 all used tesa 7475 PV2 silicone release coating test tape, and were conditioned and tested at 23±1℃ and 50±2% relative humidity. The tape was applied to the release surface of the release paper, and rolled twice back and forth at a speed of 10mm / s using a standard rubber roller with a mass of 2.00±0.01kg and a surface Shore A hardness of 80±5. The contact time was 20h at 23±1℃ and 50±2% relative humidity. After the contact time, the tape was peeled off from the release paper at a peel direction of 180° and a speed of 300mm / min. Within 5min after peeling, the tape was applied to a clean stainless steel plate, and rolled twice back and forth using the same standard rubber roller. After 20min, the adhesion after contact was measured at a peel direction of 180° and a speed of 300mm / min.
[0194] The baseline tack strength of the same specification tape, without contact with release paper, was measured using the same stainless steel plate bonding, rolling, placement, and peeling procedures, and was 18.60 N / 25 mm. The residual tack ratio was obtained by dividing the tack strength after contact by the baseline tack strength and multiplying by 100%. All samples were subjected to the same conditioning, tape bonding, rolling, contact, transfer, placement, and peeling conditions.
[0195] Table 9. Results of residual adhesion rate test:
[0196]
[0197] Analysis: The residual adhesion rates of Examples 1-10 were 92.5%-97.2%, all not less than 90%. Under the same conditions of total PHBV and dry coating amount of silicone, the residual adhesion rate of Example 6 was 97.2%, which was higher than 89.2% of Comparative Example 2 and 91.8% of Comparative Example 3.
[0198] The residual adhesion rates of Comparative Examples 4 and 5, which formed high-coverage or continuous films, were 90.6% and 91.1%, respectively, neither of which reached the level of Example 6; the dry coating weight of the silicone was 0.35 g / m². 2 The comparative example 10 showed a yield of only 78.4%. These results indicate that the combination of the PHBV microdomains within the paper, the PHBV bridging region on the release surface, and the cross-linked silicone release layer is beneficial in reducing the impact of the release process on the adhesive properties of the pressure-sensitive adhesive.
[0199] Application Example 4: Accelerated aging stability.
[0200] Experimental Description: Examples 1-10 and Comparative Examples 1-12 were respectively bonded to tesa 7475 PV2 silicone release coating test tape. Five parallel samples were prepared for each sample under each aging condition. The tape width was 25.0 ± 0.2 mm, the effective bonding length was 100.0 ± 0.5 mm, and the nominal effective bonding area was 2500 mm².2 .
[0201] The bonded sample was clamped between two parallel rigid stainless steel plates, with a total load mass including the upper plate and loading weights of 5.10 ± 0.01 kg, corresponding to a nominal average normal pressure of 20 kPa. The load mass was confirmed using a calibrated weighing device before the test and remained constant throughout the 168-hour aging period.
[0202] The first group of samples was placed in a dry heat environment at 70°C for 168 hours under the stated average normal pressure, and the second group of samples was placed in an environment at 50°C and 90% relative humidity for 168 hours under the stated average normal pressure. Both of these conditions are accelerated aging conditions set in this specification.
[0203] After aging, the load was removed, and the sample was equilibrated at 23±1℃ and 50±2% relative humidity for 4 hours. The release force after aging was then measured at a peeling direction of 180° and a speed of 300mm / min.
[0204] The aged tape, peeled from the release paper, was applied to a clean stainless steel plate within 5 minutes. It was then rolled twice back and forth using a standard rubber roller (2.00±0.01 kg, Shore A hardness 80±5). After 20 minutes, the post-aging adhesion was measured at a 180° peel direction and a speed of 300 mm / min. No further 20-hour contact testing was performed. The residual adhesion rate after aging was calculated by dividing the post-aging adhesion by 18.60 N / 25 mm and multiplying by 100%.
[0205] The release force change rate is calculated by dividing the difference between the release force after aging and the initial release force by the initial release force and then multiplying by 100%.
[0206] Table 10 Accelerated aging stability test results:
[0207]
[0208] Analysis: The release force change rates of Examples 1-10 after dry heat and wet heat treatment were 3.7%-13.7% and 6.1%-19.1%, respectively, with absolute values of change rates not exceeding 20%. The changes caused by wet heat aging were generally higher than those caused by dry heat aging. In Example 6, the dry heat and wet heat change rates were 3.7% and 6.1%, respectively, and the residual adhesion rates after aging were 96.0% and 95.1%, respectively.
[0209] Under the same total material conditions, the wet heat change rates of Comparative Example 2 and Comparative Example 3 were 28.0% and 21.5%, respectively, both higher than those of Example 6. The wet heat change rate of Comparative Example 10 was 55.0%, and the residual adhesion rate after wet heat was 65.2%, indicating that insufficient dry coating of silicone will significantly reduce the release stability after aging.
[0210] Application Example 5: Silicone maintains and cures quality.
[0211] For each test sample, a matching blank sample without crosslinked silicone was prepared simultaneously. Except for the absence of crosslinked silicone application and curing, the matching blank samples were identical to the corresponding test samples in terms of fiber slurry composition, wet-end treatment, polyhydroxyalkanoate addition path, surface primer composition, surface dry coating amount, drying conditions, and calendering conditions. The matching blank sample of Comparative Example 11 had the same polyvinyl alcohol-oxidized starch primer coating, and the matching blank sample of Comparative Example 12 had the same water glass-polyvinyl alcohol primer coating. The test samples and their matching blank samples used the same sampling locations and testing procedures.
[0212] Experimental Description: Examples 1-10 and Comparative Examples 1-12 were conditioned and tested at 23±1℃ and 50±2% relative humidity. The net coating weight of the silicone was determined using energy-dispersive X-ray fluorescence spectrometry (EDXRF) with a FINAT FTM 7. Silicon signals were measured at the same sampling location for both the test sample and the corresponding matched blank sample. The silicon signal of the test sample was subtracted from the silicon signal of the matched blank sample, and the net coating weight was calculated according to the crosslinking silicone calibration curve. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) was used for silicone depth profiling, with a 30keV Bi3 ion beam used for analysis. + The sputtered ion beam uses a 10keVAr 2000 + Cluster ions; the sputtering region is 500μm×500μm, the analysis region is a 100μm×100μm area located in the center of the sputtering region, and three independent locations are tested for each sample, with a depth profile termination depth of 40μm.
[0213] After each depth profile, the sputtering crater depth is measured using a focused ion beam scanning electron microscope at the center of the sputtering crater and at two mutually perpendicular locations. The depth calibration coefficient is obtained by dividing the average depth at the three locations by the cumulative sputtering time. The Si-C signal is defined as the positive ion spectrum normalized to the total ion count. 28 SiCH3 + Signals and 28 SiC2H5 +The sum of signals; the Si-C ratio within 8 μm is the ratio of the normalized Si-C signal integral area in the 0–8 μm range to the normalized Si-C signal integral area in the 0–40 μm range at the same measurement point. Background subtraction was performed using a matched blank sample without cross-linked silicone but with the same wet-end treatment and surface undercoat structure as the test sample; Comparative Example 11 used a matched blank sample with the same polyvinyl alcohol-oxidized starch undercoat, and Comparative Example 12 used a matched blank sample with the same water glass-polyvinyl alcohol undercoat. The results for each sample are the average and standard deviation of three independent depth profiles.
[0214] Extractable organosilicones were determined using a hexane Soxhlet extraction combined with energy-dispersive X-ray fluorescence spectrometry. 100 cm³ samples were taken from each test sample and its matched blank. 2 Three samples were prepared. The silicon signal at the same marked position was measured for both the test sample and the matched blank sample before extraction. The net silicone coating amount before extraction was obtained after subtracting the silicon signal from the matched blank sample. The test sample and the matched blank sample were placed in a Soxhlet extraction apparatus, and 150 mL of n-hexane was added. Extraction was performed for 4 hours under a cycle of 6–8 times per hour. After extraction, the samples were dried under vacuum at 60°C for 2 hours and equilibrated at 23±1°C and 50±2% relative humidity for 4 hours. The silicon signal at the same marked position was measured again. After subtracting the silicon signal from the matched blank sample that had undergone the same extraction and drying treatment, the net silicone coating amount after extraction was obtained. The extractable silicone mass fraction was calculated as the difference between the net silicone coating amount before extraction and the net silicone coating amount after extraction, divided by the net silicone coating amount before extraction and multiplied by 100%.
[0215] The silicon loss rate after friction was determined using a reciprocating linear friction procedure. The friction head was a stainless steel cylindrical head with a diameter of 20.0±0.1 mm, and the contact surface was bonded with a silicone-free EPDM rubber pad with a thickness of 2.0±0.1 mm and a Shore A hardness of 70±5. The sample size was 50 mm × 150 mm, the friction direction was parallel to the longitudinal direction of the paper, the normal load was 10.0±0.1 N, the unidirectional stroke was 100 mm, the running speed was 100 mm / s, and a total of 100 reciprocating cycles were performed.
[0216] Five parallel samples were tested for each test sample and its matching blank sample. The matching blank sample was subjected to the same rubbing procedure as the corresponding test sample. Silicon signals were measured in the same marked area using FTM 7 before and after rubbing, and the silicon signal of the matching blank sample under the same rubbing conditions was subtracted to obtain the net silicone coating amount before and after rubbing. The silicone loss rate after rubbing was calculated as the difference between the net silicone coating amount before and after rubbing, divided by the net silicone coating amount before rubbing, and multiplied by 100%. Pinholes were developed using methylene blue and measured at 100cm intervals. 2 Area statistics.
[0217] Table 11 Results of silicone retention and curing quality tests:
[0218]
[0219] Note: The Si-C ratio within 8 μm, extractable organosilicon mass fraction, and silicon loss rate after friction in Table 11 are all results after deducting the corresponding unsiliconized matching blanks. Comparative Example 11 has had its background signal removed from the polyvinyl alcohol-oxidized starch primer structure, and Comparative Example 12 has had its inorganic silicon background signal removed from the water glass-polyvinyl alcohol primer structure.
[0220] Analysis: The Si-C ratio within 8μm in Examples 1–10 was 84.8%–94.1%, the extractable organosilicon mass fraction was 1.8%–4.4%, the silicon loss rate after friction was 0.8%–2.3%, and the number of pinholes was 0–5 per 100cm. 2 In Example 6, the Si-C ratio within 8 μm was 94.1%, the extractable organosilicon mass fraction was 1.8%, the silicon loss rate after friction was 0.8%, and no pinholes were detected.
[0221] The Si-C proportions within 8 μm of Comparative Examples 1, 6, and 8 were 68.6%, 71.6%, and 65.7%, respectively; the extractable organosilicon mass fraction of Comparative Example 10 was 9.5%, the silicon loss rate after friction was 8.4%, and the number of pinholes was 27 / 100 cm. 2 Comparative Examples 5 and 9, which formed high-coverage surfaces or increased PHBV dosage, did not achieve further improvement in all silicone retention and curing quality indicators.
[0222] Application Example 6: Adaptability to continuous production.
[0223] Experimental description: Examples 6, 7 and 9 were subjected to an 8-hour wet end cycling test; Examples 6, 7, 9, Comparative Example 3 and Comparative Example 11 were subjected to an 8-hour continuous roll-to-roll surface treatment, coating and siliconization test under the conditions of a width of 280 mm and a speed of 5 m / min.
[0224] The initial retention rate of PHBV was measured at 2h, 4h, 6h, and 8h of stable operation in the wet end. Three independent cellulose paper substrates were obtained at each sampling point, and five locations were selected along the horizontal direction on each substrate. The total mass of PHBV in the 0–100%T region was determined using the aforementioned confocal Raman microscopy absolute quantitative method. The initial retention rate of PHBV was calculated by dividing the measured mass of PHBV in the wet-end formed paper substrate by the mass of PHBV added based on the same paper area and multiplying by 100%. The results listed in Table 12 are the arithmetic mean of the four sampling points.
[0225] Chemical oxygen demand (COD) of white water was determined using a dichromate digestion spectrophotometric method. 2.00 mL of homogeneous white water sample was added to a 2125925 COD digestion reagent tube and digested at 150±2℃ for 120 min. After cooling, the COD was measured at 620 nm. Three parallel white water samples were prepared for each sample. The blank without added PHBV had the same wet-end formulation, shear history, and cycling conditions as in the examples, except for the absence of the aqueous dispersion of poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester. Quality control was performed daily using a 100 mg / L COD standard solution, with a standard solution recovery rate of 95%–105%. The increase in white water COD was calculated by dividing the difference in COD between the PHBV-added sample and the blank without PHBV by the blank COD and multiplying by 100%.
[0226] After the continuous roll-to-roll operation reached a stable stage, full-width samples were taken at 2h, 4h, 6h, and 8h, at positions of 10%, 30%, 50%, 70%, and 90% of the effective width of 280mm. Based on the amount of surface treatment layer applied and retained at the five transverse positions at each time point and the net amount of silicone coating, the cross-sectional coefficient of variation was calculated. The results listed in Table 12 are the arithmetic mean of the four sampling time points. In Examples 6, 7, 9, and Comparative Example 3, the surface treatment layer was a PHBV surface treatment layer, and in Comparative Example 11, the surface treatment layer was a polyvinyl alcohol-oxidized starch base coating.
[0227] Longitudinal sampling of release force was conducted at the center of the banner, with sampling every hour from the start of stable operation, for a total of 8 sampling points. At each sampling point, 5 parallel samples with a width of 25 mm were obtained. The initial release force was determined according to the method in Application Example 2, and the longitudinal coefficient of variation was calculated based on the average release force at the 8 sampling points. Each coefficient of variation was calculated by dividing the standard deviation by the average value and multiplying by 100%.
[0228] After 8 hours of continuous operation, all removable deposits on the coating head components were collected without using cleaning water, dried at 105±2℃ to constant weight, and then weighed. The power consumption for drying was calculated by dividing the power consumption of the drying system during continuous operation by the effective coating area during the same period, and converted to a value per 1000m². 2 Electricity consumption; the number of paper breaks is counted based on paper web breakage events that occur during 8 hours of continuous operation.
[0229] Table 12 Results of Continuous Production Adaptability Test:
[0230]
[0231] Note: Table 12 only lists samples that actually completed the 8-hour wet-end circulation or continuous roll-to-roll test. Examples 6, 7, and 9 underwent both the 8-hour wet-end circulation test and the continuous roll-to-roll test; Comparative Examples 3 and 11 only underwent the continuous roll-to-roll test, and PHBV was not added to their wet end, therefore the first-pass retention rate and white water COD increase rate are not applicable. The remaining examples and comparative examples were not included in the continuous production adaptability test of this project, and therefore are not listed in the table.
[0232] Table 13 Measured COD Results of White Water:
[0233]
[0234] Note: "—" indicates that the relative blank increase rate is not calculated if PHBV blank is not included.
[0235] Analysis: The average COD of the white water without PHBV blank in Table 13 was 83.80 mg / L. The average COD of the white water in Examples 6, 7, and 9 were 89.50 mg / L, 88.73 mg / L, and 88.33 mg / L, respectively, with a relative increase rate of 5.4%–6.8%, consistent with Table 12. The first-pass PHBV retention rate of the three examples was 84.8%–87.2%.
[0236] Under the conditions of 280 mm width, 5 m / min speed, and 8 h of operation, no paper breaks occurred in Examples 6, 7, and 9, and the horizontal coefficients of variation for the amount of PHBV applied and retained on the surface and the net amount of silicone coating were all below 5%. Comparative Example 3 had higher horizontal coefficients of variation for the amount of PHBV applied and retained on the surface, higher coating head deposition, and higher drying power consumption than the three examples. Comparative Example 11 had a polyvinyl alcohol-oxidized starch base coating, and its coating head deposition, drying power consumption, and longitudinal coefficients of variation for release force were the highest among the continuously running samples, and it experienced one paper break.
[0237] Experimental results and analysis.
[0238] The total PHBV content in Example 6, Comparative Examples 2 and 3 was 0.45 g / m³. 2 The dry coating weight of the silicone is 0.60 g / m². 2Example 6 employs a dual-zone distribution structure consisting of PHBV microdomains within the paper and PHBV bridging regions on the release surface. Its initial release force is 21.4 cN / 25 mm, coefficient of variation is 4.3%, residual adhesion rate is 97.2%, release force change rate under damp heat aging is 6.1%, and Si-C ratio within 8 μm is 94.1%. Comparative Example 2, which only incorporates PHBV within the paper, has corresponding values of 32.8 cN / 25 mm, 9.7%, 89.2%, 28.0%, and 72.8%; Comparative Example 3, which only incorporates PHBV on the release surface, has corresponding values of 25.6 cN / 25 mm, 6.6%, 91.8%, 21.5%, and 86.5%. Under the same total material conditions, the dual-zone distribution structure achieves lower release force fluctuations, higher residual adhesion rates, and lower deep silicone migration.
[0239] Comparative Example 4 and Example 6 have the same total PHBV and silicone dry coating amount, but Comparative Example 4 has a release surface PHBV projection coverage of no less than 90% and a fiber exposed area ratio of no more than 5%. The residual adhesion rate of Comparative Example 4 is 90.6%, the release force change rate under wet heat aging is 25.5%, and the extractable silicone mass fraction is 5.4%, all of which are lower than those of Example 6. Comparative Example 5 uses 1.20 g / m³... 2 The surface-mounted PHBV continuous film exhibited a residual adhesion rate of 91.1%, a release force change rate of 18.8% under damp heat aging, and an extractable organosilicon mass fraction of 5.0%. These results indicate that increasing the surface coverage or forming a thicker continuous film did not yield superior overall performance compared to the low-bridged structure.
[0240] Examples 6, 7, and 9 were run continuously for 8 hours at a width of 280 mm and a speed of 5 m / min. The initial PHBV retention rate was 84.8%–87.2%, the increase rate of white water COD relative to blank was 5.4%–6.8%, and the coefficient of variation of the horizontal width of the surface PHBV applied and retained amount and the net silicone coating amount were both less than 5%, with no paper breaks occurring. These results indicate that the wet-end addition, low-amount application at the release surface, and silicone curing process are suitable for continuous production.
[0241] From the trend of content change, when the wet-end added route retained PHBV dry solids increased from 0.10 g / m in Example 6, it showed that... 2 Reduced to 0.02 g / m² in Comparative Example 7. 2 At that time, the initial release force increased from 21.4 cN / 25 mm to 28.9 cN / 25 mm, the residual adhesion decreased from 97.2% to 89.8%, the change rate of release force under humid heat aging increased from 6.1% to 26.3%, and the proportion of Si-C within 8 μm decreased from 94.1% to 79.8%; when the PHBV dry solids applied to and retained on the surface decreased from 0.35 g / m² in Example 6 to 0.12 g / m² in Comparative Example 8. 2At that time, the initial release force increased to 38.9 cN / 25 mm, the residual adhesion rate decreased to 85.5%, the release force change rate under damp heat aging increased to 40.1%, and the Si-C ratio within 8 μm decreased to 65.7%.
[0242] Comparative Example 9 increased the amount of PHBV dry solids retained in the wet-end addition route and the amount of PHBV dry solids applied and retained on the surface to 0.20 g / m², respectively. 2 and 0.70g / m 2 The total dry solids content of PHBV reached 0.90 g / m³. 2 Although the initial release force decreased to 17.8 cN / 25 mm, the residual adhesion rate was 92.0%, the release force change rate under humid heat aging was 16.9%, and the extractable organosilicon mass fraction was 4.9%, failing to achieve a comprehensive improvement corresponding to the increase in PHBV.
[0243] Under the compared overall formulation and process combinations, the surface-applied and retained PHBV dry solids of Examples 9, 10, and 5 were 0.24 g / m³, respectively. 2 0.48g / m 2 and 0.55g / m 2 The PHBV projection coverage of the release surface was 31%, 80%, and 79%, respectively, and the initial release forces were 27.8 cN / 25 mm, 20.3 cN / 25 mm, and 19.6 cN / 25 mm, respectively. The Si-C ratio within 8 μm was 84.8%, 92.1%, and 92.4%, respectively. This indicates that increasing the amount of PHBV dry solids applied and retained on the surface within the specified process range generally increases the release surface coverage and near-surface silicone retention. However, this trend is also affected by the PHBV dry solids retained along the wet-end addition route, the calendering conditions, and the amount of silicone dry coating.
[0244] Comparative Example 10 has the same PHBV dosage and spatial structure as Example 6, except that the dry coating amount of silicone is reduced from 0.60 g / m² to 0.35 g / m². Its initial release force increases to 46.7 cN / 25 mm, the residual adhesion rate decreases to 78.4%, the release force change rate under wet heat aging increases to 55.0%, the extractable silicone mass fraction increases to 9.5%, and 27 pinholes / 100 cm² appear. Example 7 still meets the requirements of residual adhesion rate not less than 90% and absolute value of release force change rate under aging not greater than 20% when the dry coating amount of silicone is 0.45 g / m², indicating that 0.45 g / m² is the lower limit of the dry coating amount of silicone that has been verified in this group of experiments.
[0245] In summary, the total PHBV should be controlled within the range of 0.25–0.70 g / m³. 2Simultaneously, it forms discrete PHBV microdomains within the cellulose paper base and multiple PHBV bridging regions on the release surface that are separated or partially connected at fiber intersections, openings, or throats. This reduces the migration of silicone into the deeper layers of the paper base with lower PHBV and silicone dosages, maintains residual adhesion and aging release stability, and also takes into account continuous coating and siliconization operations.
[0246] By further controlling the absolute mass of PHBV in the release surface area and the area outside the release surface area, the micro-morphology of PHBV in the paper, and the size and coverage of the PHBV bridging area on the release surface, the repeatability of the dual-zone spatial structure and the stability of the near-surface layer of organosilicon can be further improved.
[0247] This group of experiments used tesa 7475 PV2 silicone release coating test tape to verify the initial release performance, residual adhesion rate and aging stability of the high-performance release paper prepared in Examples 1 to 10 when in contact with the tape; labels, industrial tapes and die-cutting materials with the same or similar acrylic pressure-sensitive adhesive systems were adapted according to the corresponding product conditions.
[0248] Those skilled in the art should understand that the above embodiments are merely exemplary and not intended to limit the scope of the invention. The scope of protection of the present invention is defined by the appended claims. Any modifications, equivalent substitutions, improvements, etc., made to the technical solutions of the present invention within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A high-performance release paper, characterized in that, The high-performance release paper includes a cellulose paper base and an addition-type cross-linked silicone release layer. The cellulose paper base has a release surface, and the addition-type cross-linked silicone release layer is disposed on the release surface. The cellulose paper base contains one or more polyhydroxy fatty acid esters, which are collectively referred to as target polyhydroxy fatty acid esters. The target polyhydroxy fatty acid esters form discrete intrapaper polyhydroxy fatty acid ester microdomains inside the cellulose paper base and form multiple release surface polyhydroxy fatty acid ester bridging regions that are separated from or partially connected to each other on the release surface. The release surface polyhydroxy fatty acid ester bridging regions are located at fiber intersections, openings, or throats. Taking the release surface as the starting point in the thickness direction and the thickness of the cellulose paper base as T, within a region greater than 20%T and not greater than 100%T from the release surface, the spatial unit formed by the target polyhydroxyalkanoate is defined as a target polyhydroxyalkanoate domain. The target polyhydroxyalkanoate domain with a maximum Feretta diameter of not less than 20 μm and an aspect ratio of not less than 5 is defined as a sheet-like polyhydroxyalkanoate domain. Except for the sheet-like polyhydroxyalkanoate domains, the target polyhydroxyalkanoate exists as paper-in-paper polyhydroxyalkanoate microdomains with an equivalent diameter of 0.2–5 μm. The sum of the projected areas of the sheet-like polyhydroxyalkanoate domains accounts for no more than 5% of the sum of the projected areas of all the target polyhydroxyalkanoate domains within the region. The total amount of the target polyhydroxyalkanoate in the cellulose paper base is 0.25–0.70 g / m³. 2 The dry coating weight of the addition-cured crosslinked silicone release layer is 0.45–0.75 g / m². 2 .
2. The high-performance release paper according to claim 1, characterized in that, The area no more than 20%T from the release surface is defined as the release surface surface area, and the area more than 20%T but no more than 100%T from the release surface is defined as the area outside the surface area. The amount of the target polyhydroxyalkanoate in the release surface region is 0.20–0.55 g / m². 2 The amount of the target polyhydroxyalkanoate in the region outside the surface layer is 0.04–0.18 g / m². 2 .
3. The high-performance release paper according to claim 1, characterized in that, Based on the number of polyhydroxyalkanoate microdomains within the paper, the proportion of polyhydroxyalkanoate microdomains in contact with the cellulose fiber entity is not less than 70%.
4. The high-performance release paper according to claim 1, characterized in that, The equivalent diameter of the polyhydroxyalkanoate bridging region on the release surface is 3 to 30 μm, and the projection coverage of the target polyhydroxyalkanoate on the release surface is 30% to 80%.
5. The high-performance release paper according to claim 1, characterized in that, The target polyhydroxy fatty acid ester includes at least poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester, wherein the poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester accounts for no less than 90 wt% of the total mass of all polyhydroxy fatty acid esters contained in the high-performance release paper, and the content of 3-hydroxyvalerate structural units in the poly(3-hydroxybutyrate-3-hydroxyvalerate) copolyester is 3 to 20 mol.
6. A high-performance release film, characterized in that, The high-performance release film includes a polymer support film, a composite adhesive layer, and the high-performance release paper according to any one of claims 1 to 5. The composite adhesive layer is disposed between the polymer support film and the side of the high-performance release paper facing away from the addition-cruising cross-linked silicone release layer. The addition-cruising cross-linked silicone release layer constitutes the release surface of the high-performance release film.
7. A release paper to be siliconized, characterized in that, The release paper to be silicified includes a cellulose paper base with a release surface, the release surface constituting the exposed surface of the release paper to be silicified; The cellulose paper base contains one or more polyhydroxy fatty acid esters, which are collectively referred to as target polyhydroxy fatty acid esters. The target polyhydroxy fatty acid esters form discrete intrapaper polyhydroxy fatty acid ester microdomains inside the cellulose paper base and form multiple release surface polyhydroxy fatty acid ester bridging regions that are separated from or partially connected to each other on the release surface. The release surface polyhydroxy fatty acid ester bridging regions are located at fiber intersections, openings, or throats. Taking the release surface as the starting point in the thickness direction and the thickness of the cellulose paper base as T, within a region greater than 20%T and not greater than 100%T from the release surface, the spatial unit formed by the target polyhydroxyalkanoate is defined as a target polyhydroxyalkanoate domain. The target polyhydroxyalkanoate domain with a maximum Feretta diameter of not less than 20 μm and an aspect ratio of not less than 5 is defined as a sheet-like polyhydroxyalkanoate domain. Except for the sheet-like polyhydroxyalkanoate domains, the target polyhydroxyalkanoate exists as paper-in-paper polyhydroxyalkanoate microdomains with an equivalent diameter of 0.2–5 μm. The sum of the projected areas of the sheet-like polyhydroxyalkanoate domains accounts for no more than 5% of the sum of the projected areas of all the target polyhydroxyalkanoate domains within the region. The total amount of the target polyhydroxyalkanoate in the cellulose paper base is 0.25–0.70 g / m³. 2 .
8. A polyhydroxyalkanoate-based barrier coating composition for preparing high-performance release paper having polyhydroxyalkanoate microdomains within the paper and polyhydroxyalkanoate bridging regions on the release surface, characterized in that, The polyhydroxyalkanoate-based barrier coating composition is an aqueous composition comprising water and dry solids components, and the solid content of the polyhydroxyalkanoate-based barrier coating composition is not less than 8 wt% and less than 20 wt%. The dry solids component includes polyhydroxy fatty acid esters and one or more water-based coating aids. The polyhydroxy fatty acid esters in the dry solids component are defined as target polyhydroxy fatty acid esters. The content of the target polyhydroxy fatty acid esters is 91.5 to 99.5 wt% based on the total mass of the dry solids component, and the content of non-polyhydroxy fatty acid ester film-forming polymers in the dry solids component is not higher than 5 wt%.
9. A method for preparing high-performance release paper, characterized in that, The one or more polyhydroxy fatty acid esters used in steps 1 and 2 below are collectively referred to as target polyhydroxy fatty acid esters, and the preparation method includes the following steps: Step 1: Add the aqueous dispersion containing the target polyhydroxy fatty acid ester to the fiber slurry, and then form, press and dry it to form discrete polyhydroxy fatty acid ester microdomains within the cellulose paper base, thereby obtaining the cellulose paper base. Step 2: Apply an aqueous composition containing the target polyhydroxy fatty acid ester to the release surface of the cellulose paper base, and after drying and calendering, the target polyhydroxy fatty acid ester forms multiple release surface polyhydroxy fatty acid ester bridging regions that are separated or partially connected to each other at fiber intersections, openings or throats, to obtain the release paper to be siliconized. Step 3: Apply and cure addition-type crosslinked silicone on the release surface of the release paper to be siliconized to form an addition-type crosslinked silicone release layer, thereby obtaining the high-performance release paper; The total dry solids of the target polyhydroxyalkanoate retained in the cellulose paper base after steps 1 and 2 are 0.25–0.70 g / m³. 2 The dry coating weight of the addition-cured crosslinked silicone release layer is 0.45–0.75 g / m². 2 .
Citation Information
Patent Citations
A PHA water-based coating and its preparation method and application
CN119777197A
A PHA / PVA nano-scale paper-based barrier emulsion and its preparation method and application
CN120250392B
Bio-based PHA oil-blocking and moisture-permeable coating for hamburger paper, coated paper and preparation method
CN120759147B
Latex of poly- beta -hydroxyalkanoates for treating fiber constructs and coating paper
US5451456A
Release base paper having silicate-containing primer coats
US5807781A